Distributed Temperature Sensing as a downhole tool in hydrogeology. Issue 12 (22nd December 2016) - Bense, V. F.; Read, T.; Bour, O.; Le Borgne, T.; Coleman, T.; Krause, S.; Chalari, A.; Mondanos, M.; Ciocca, F.; Selker, J. S.
Abstract: Distributed Temperature Sensing (DTS) technology enables downhole temperature monitoring to study hydrogeological processes at unprecedentedly high frequency and spatial resolution. DTS has been widely applied in passive mode in site investigations of groundwater flow, in‐well flow, and subsurface thermal property estimation. However, recent years have seen the further development of the use of DTS in an active mode (A‐DTS) for which heat sources are deployed. A suite of recent studies using A‐DTS downhole in hydrogeological investigations illustrate the wide range of different approaches and creativity in designing methodologies. The purpose of this review is to outline and discuss the various applications and limitations of DTS in downhole investigations for hydrogeological conditions and aquifer geological properties. To this end, we first review examples where passive DTS has been used to study hydrogeology via downhole applications. Secondly, we discuss and categorize current A‐DTS borehole methods into three types. These are thermal advection tests, hybrid cable flow logging, and heat pulse tests. We explore the various options with regards to cable installation, heating approach, duration, and spatial extent in order to improve their applicability in a range of settings. These determine the extent to which each method is sensitive to thermal properties, vertical in‐well flow, or natural gradient flow. Our review confirms that the application of DTS has significant advantages over discrete point temperature measurements, particularly in deep wells, and highlights the potential for further method developments in conjunction with other emerging hydrogeophysical tools. Key Points: Distributed Temperature Sensing in subsurface applications allows the monitoring subsurface hydrology in unprecedented spatiotemporal detail The specific limitations of DTS measurements need to be taken into account in the design of field installations The application of DTS in subsurface hydrology is still under development